The Impact of Working from Home during a Pandemic Against Employee Performance (Exploratory Study) - Sunardi Sunardi (Universitas Pamulang, 2022)
Working from home (WFH) is an efficient solution during the Covid-19 pandemic to maintain productivity and avoid transmission of the coronavirus. However, the pattern of work done from home is different from work done in the office. Of course, the performance produced by employees will be different. Thus, in order to maintain a balance between work and employee commitment, various aspects of WFH are studied. In this study, there were four aspects that were studied during the WFH to see employee performance, namely aspects of space, time, social, and economy. In addition, this study also aims to analyze the advantages and disadvantages of WFH during the Covid-19 pandemic from an employee perspective so that it can be used as evaluation material for the implementation of WFH in the Secretariat of the Language Development and Development Agency. This study used an exploratory method and the data were analyzed descriptively. The survey found six advantages of WFH, namely (1) time flexibility; (2) time efficiency; (3) financial efficiency; (4) energy efficiency; (5) quality time with family; and (6) increased productivity and ten WFH deficiencies, namely (1) lack of facilities; (2) increase in household operational costs; (3) miscommunication; (4) difficulties in supervising the work of employees; (5) difficulty completing work without face to face; (6) difficulty determining priorities; (7) unclear work deadlines; (8) loss of work motivation; (9) the number of distractions at work; and (10) data insecurity.